2017
DOI: 10.1016/j.jdermsci.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Non-pathogenic pemphigus foliaceus (PF) IgG acts synergistically with a directly pathogenic PF IgG to increase blistering by p38MAPK-dependent desmoglein 1 clustering

Abstract: Background-Pemphigus foliaceus (PF) is an autoimmune blistering disease caused by autoantibodies (Abs) against desmoglein 1 (Dsg1). PF sera contain polyclonal Abs which are heterogeneous mixture of both pathogenic and non-pathogenic Abs, as shown by isolation of monoclonal Abs (mAbs).Objective-To investigate how pathogenic and non-pathogenic anti-Dsg1 Abs contribute to blister formation in PF.Methods-Using organ-cultured human skin, we compared the effect of a single pathogenic antiDsg1 IgG mAb, a single non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
3
32
0
1
Order By: Relevance
“…Antibodies selectively targeting Dsg1 and Dsg3 are sufficient to cause acantholysis and skin vesiculation in mice and in ex vivo human skin (Di Zenzo et al, 2012;Eming et al, 2014;Ishii et al, 2008;Langenhan et al, 2014;Payne et al, 2005;Saito et al, 2012;Spindler et al, 2013;Yamagami et al, 2010;Yeh et al, 2006). PV-IgG have been shown to induce direct inhibition of Dsg3 binding, and several signaling pathways downstream of antibody binding including p38 mitogen-activated protein kinase, Ca 2þ , protein kinase C, Src, EGFR, RhoA, c-Myc, glycogen synthase kinase 3, Pg, and caspases were shown to be involved in the loss of keratinocyte cohesion in PV, pemphigus foliaceus, and atypical pemphigus (Bektas et al, 2013;Berkowitz et al, 2006Berkowitz et al, , 2008Caldelari et al, 2001;Chernyavsky et al, 2007;Cirillo et al, 2010Cirillo et al, , 2014Dehner et al, 2014;Frusic-Zlotkin et al, 2006;Li et al, 2009;Luyet et al, 2015;Mao et al, 2011Mao et al, , 2014Saito et al, 2012;Sánchez-Carpintero et al, 2004;Sayar et al, 2014;Spindler et al, 2011Waschke et al, 2006;Williamson et al, 2006;Yoshida et al, 2017).…”
Section: Role Of Autoantibodies Directed Against Desmoglein 1 and Desmentioning
confidence: 99%
“…Antibodies selectively targeting Dsg1 and Dsg3 are sufficient to cause acantholysis and skin vesiculation in mice and in ex vivo human skin (Di Zenzo et al, 2012;Eming et al, 2014;Ishii et al, 2008;Langenhan et al, 2014;Payne et al, 2005;Saito et al, 2012;Spindler et al, 2013;Yamagami et al, 2010;Yeh et al, 2006). PV-IgG have been shown to induce direct inhibition of Dsg3 binding, and several signaling pathways downstream of antibody binding including p38 mitogen-activated protein kinase, Ca 2þ , protein kinase C, Src, EGFR, RhoA, c-Myc, glycogen synthase kinase 3, Pg, and caspases were shown to be involved in the loss of keratinocyte cohesion in PV, pemphigus foliaceus, and atypical pemphigus (Bektas et al, 2013;Berkowitz et al, 2006Berkowitz et al, , 2008Caldelari et al, 2001;Chernyavsky et al, 2007;Cirillo et al, 2010Cirillo et al, , 2014Dehner et al, 2014;Frusic-Zlotkin et al, 2006;Li et al, 2009;Luyet et al, 2015;Mao et al, 2011Mao et al, , 2014Saito et al, 2012;Sánchez-Carpintero et al, 2004;Sayar et al, 2014;Spindler et al, 2011Waschke et al, 2006;Williamson et al, 2006;Yoshida et al, 2017).…”
Section: Role Of Autoantibodies Directed Against Desmoglein 1 and Desmentioning
confidence: 99%
“…However, for the combination of IgG against the NC16A domain and the C-terminus, COL17 depletion was significantly enhanced ( Figure 5). The enhancement of the pathogenicity by nonpathogenic IgG has been reported in pemphigus vulgaris (Kawasaki et al, 2006) and pemphigus foliaceus (Yoshida et al, 2017). The depletion activity of pathogenic mAbs against Dsg3 is known to be boosted when those mAbs act in combination with nonpathogenic mAbs (Yamamoto et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…In a passive transfer mouse model, p38MAPK inhibition impedes blistering by PV IgG . In an ex vivo human organ culture model utilizing human skin, IgG induced p38MAPK phosphorylation and downstream desmoglein clustering, but was not essential for blistering . Mao et al .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
“…97 In an ex vivo human organ culture model utilizing human skin, IgG induced p38MAPK phosphorylation and downstream desmoglein clustering, but was not essential for blistering. 98 Mao et al 99 further demonstrated that mice with p38 deletion continue to develop suprabasilar blisters in the presence of PV IgG, suggesting that p38MAPK activation may be secondary to the loss of intercellular adhesion and not the root cause.…”
Section: Cell Signalling Targetsmentioning
confidence: 99%